Potential Risk of Virus Carryover by Fabrics of Personal Protective Gowns - Katoh, Iyoko; Tanabe, Fuminori; Kasai, Hirotake; Moriishi, Kohji; Shimasaki, Noriko; Shinohara, Katsuaki; Uchida, Yukiko; Koshiba, Tomoko; Arakawa, Soichi; Morimoto, Michiko (Frontiers in Public Health, 2019)
Personal protective gowns and coveralls are classified based on barrier efficiency that validates protection from fluid penetration under certain pressures. Materials standardized in this system have been found suitable for emergency medical practices confronting highly contagious diseases. Nevertheless, adhesion of blood, and body fluids from virus-infected patients to the surface of protective clothing still imposes a risk of pathogen transmission in the process of doffing, or undressing. We performed a small-scale experiment to test the possibility of infectious virus carryover on the surface of different fabrics used in commercially available protective gowns. Application of a lentivirus vector that expresses green fluorescent protein allowed easy monitoring of infectious viral loads on fabrics. Results indicate that fabrics of level-3 surgical gowns serve better to reduce virus transmission compared to fabrics of chemical protective clothing with the same or higher barrier efficiency. Analysis of sliding angles provided indexes of fluid repellency, which were inversely related to virus carryover potentials. Droplets of infectious body fluids may easily roll off fabrics with water-repellent finishing. Thus, virus carryover is a measurable risk factor to be considered for better choice of personal protective clothing.